The Relationship of Breastfeeding Mother's Attitude and Motivation with Success in Exclusive Breastfeeding in the Working Area of the Bunga Jadi Public Health Center Year 2023 - Corniawati, Inda; Nursari Abdul Syukur; Sovranita (PT FORMOSA CENDEKIA GLOBAL, 2023)
Exclusive breastfeeding is influenced by many factors, namely family support, the mother's attitude, the role of health workers, emotional support, information to the mother, the mother's knowledge, the and mother's motivation. These factors are some of the many factors that influence exclusive breastfeeding. The research methodology utilized is analytical with a cross-sectional design. The study's population comprises 560 mothers who have infants and toddlers aged between 6 and 24 months. The sampling technique applied is simple random sampling, involving the random selection of 94 individuals from the population. This method ensures a fair representation of the research.The results of this study showed that there was a relationship between the attitude and motivation of breastfeeding mothers with success in exclusive breastfeeding in the working area of the Bunga Jadi Public Health Center in 2023, with each p-value of 0.000 < α: 0.05. Breastfeeding is often not achieved because many parents think that their children are hungry and will sleep soundly if they are given food. They also think that in ancient times they were fed bananas from a few days old, and there were no problems. This wrong view often supresses new mothers who do not have strong understanding and principles. Health workers at the public health center provide material about exclusive breastfeeding both during counseling and in posyandu activities